Acute Hepatitis in the DRESS Syndrome - Oliveira, AM (2017)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe, idiosyncratic reaction characterized by diffuse maculopapular rash, facial edema, lym- phadenopathy, fever, eosinophilia and/or other leukocyte abnormalities, and involvement of internal organs as liver, kidney, heart and lung. Diagnosing this entity is speciﬁcally complicated due to the multiplicity of organs involved. DRESS syndrome must be recognized promptly and the causative drug withdrawn in order to improve patient outcomes. Indeed, it is a potentially life-threatening condition, with a reported mortality between 5 and 20%. We describe a case of a 22-year old woman admitted to our hospital with acute diffuse, pruritic rash associated with crampy abdominal pain, vomiting, diarrhea and fever three weeks after starting sulfasalazine therapy. Initially, laboratory parameters revealed normal white blood cell count and normal liver enzymes, but during hospitalization, eosinophilia developed and liver enzymes, including transaminases and cholestatic parameters, dramatically increased. The diagnostic of DRESS syn- drome was made and sulfasalazine was withdrawn and as there were signs of disease severity, systemic corticotherapy was initiated, with gradually improvement of the rash and symptoms resolution. The patient was discharged home after thirty days of hospitalization.